تحديد خصائص أكسيد القصدير ) (SnO2المطعم بالحديد )(F - سقني, ليلـى (My University, 2016)
In this work , we studied structural, electrical, and optical characterization of undoped tin oxide (SnO2) and iron (Fe) doped (SnO2) thin films , Which have been deposited from tin chloride (SnCl2) and iron chloride (FeCl3) onto glass substrates by spray pyrolysis technique. Samples were deposited for 3 minutes at the substrate temperature of 480°C. The doping concentration of (Fe) was varied from 1 to 10 wt (%) in solution . X-ray diffraction (XRD) has shown polycrystalline structure according to Tetragonal , Rutile (SnO2) structure with (211) as preferential orientation for iron (Fe) doped (SnO2) thin films. The optical transmittance of (Fe:SnO2) films in visible region increases from 68% to 75%. The sheet resistance (Rsh) varied from )522.1122 Ω) to )15111.51 Ω) for Fe-doping in the range 0-6 wt (%).The optical band gap (Eg) increased from (0.11eV) to (3.99eV) with increasing of the concentration of Fer (Fe) dopants
مذكرة ماستر فيزياء
Keywords: Tin oxide (SnO2), Spray pyrolysis, Thin films, Iron (Fe), X-ray diffraction (XRD; Dioxyde d'étain (SnO2), Spray pyrolyse, Couche mince, Fer (Fe), Diffraction des rayons X (DRX)